Language policy in speech acts of the characters in the film Aisyah Biarkan Kami Bersaudara - Morelent, Yetty; Yulisna, Risa; Syofiani, Syofiani; Isnanda, Romi; Khalida, Sarah (Universitas Jambi, Indonesia, 2026)
This study examines the role of politeness in language as a reflection of the speaker’s ethics and character, both in everyday communication and film dialogues. The film Aisyah Biarkan Kami Bersaudara was selected due to its depiction of a Muslim teacher in a predominantly non-Muslim area, delivering messages of tolerance, unity, and humanity. The research aims to identify the types of speech acts, describe politeness strategies, and analyze violations of politeness in the film’s dialogue. Using a qualitative approach with descriptive methods, data were collected through transcription and analyzed using Searle's speech act theory and Leech's politeness principles. The study found 452 speech acts, with directive acts being the most prevalent. Politeness was observed in 47 instances, with the sympathy maxim being dominant, while 20 violations were identified, mainly involving the maxim of agreement. The findings contribute to the development of pragmatic studies and cross-cultural communication.